A violência simbólica no contexto da modernização da agricultura: reflexos no direito à alimentação - Pereira, Douglas Otoni (2019)
The theme of this dissertation is symbolic violence in the context of the modernization of agriculture: reflexes in the direct to food. The new patterns of food consumption reached their most destructive force after the process of agricultural modernization, which proved unable to promote the just distribution of food and turned food into a mechanism of symbolic domination and violence. This study aims to demonstrate how the strategies of domination relations are able to form and condition the subjects of law within a symbolic universe, where the promise of social justice and material progress cover the protection of the values of the dominant groups related to agribusiness. It also deals with legal experience within the historical processes in which it is inserted, demonstrating the role of law in the light of disputes over economic hegemony and the struggle for power in the process of modernization of agriculture. Using the methodology of bibliographical, exploratory and documentary research, the first chapter sought to define symbolic violence and to evaluate how agribusiness used a set of ideologies to transform the vision of the world and achieve its projects. Next, it was verified how the use of symbolic systems and resources of rhetoric allowed to the different instances of the State to extend forms of development much more extensive than those allowed by the fundamental rules of a constitutional order. Finally, it was tried to understand how the development of the agribusiness removed the participation of the Judiciary Power in the realization of the human right to adequate food.